2022
DOI: 10.1088/1402-4896/ac6e51
|View full text |Cite
|
Sign up to set email alerts
|

Electrically MHD Casson nanofluid flow and entropy exploration under the influence of the viscous dissipation, radiation, and higher-order chemical reaction

Abstract: The current study aims at studying the viscous dissipation and chemical reaction of higher-order Casson nanofluid flow and entropy exploration along with MHD and electric field influences. The PDE guiding the model is transformed into nonlinear ODE by applying adequate similarity transformations. Further, the equations are worked out using the Keller Box method. The influence of several parameters β, Ha, Er, Kr, Nt, Nb, Sc, Ec, Pr, Rd is observed by constructing velocity, temperature, and concentration graphs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Abo-Dahab et al [2] explicated Casson nanofluid flow surpassing a nonlinearly stretching sheet under consequences of the chemical reaction and magnetic field. Ganesh et al [3] examined Casson nonofluid flow by deeming consequences of electric and magnetic fields. They presumed diagnostic consequences of viscous dissipation and thermal radiation assigned in the energy equation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abo-Dahab et al [2] explicated Casson nanofluid flow surpassing a nonlinearly stretching sheet under consequences of the chemical reaction and magnetic field. Ganesh et al [3] examined Casson nonofluid flow by deeming consequences of electric and magnetic fields. They presumed diagnostic consequences of viscous dissipation and thermal radiation assigned in the energy equation.…”
Section: Introductionmentioning
confidence: 99%
“…Ganesh et al. [3] examined Casson nonofluid flow by deeming consequences of electric and magnetic fields. They presumed diagnostic consequences of viscous dissipation and thermal radiation assigned in the energy equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data showed that increasing the Darcy number directly with the modified Rayleigh number and fin dimension increased the average Nusselt number. They also reviewed current research for natural convection in cavities of different shapes with internal hosts, such as the MHD effect and double diffusion [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dharmaiah G., et al in (2020) present Magneto-titanium alloy nano liquid Hall and ion slip impact with diffusion, thermodynamics, and radiation absorption. Raghavendra G Ganesh et al (2022) invented Casson nanofluid flow and entropy exploration under the influence of the viscous dissipation, radiation, and higher-order chemical reaction. Dharmaiah, G et al, (2018) discussed a vertical plate with a radiative and impulsive surface is passed by a nanofluid in MHD boundary layer flow, transferring heat.…”
Section: Introductionmentioning
confidence: 99%